The Study of Flipped-Classroom for Pre-Service Science Teachers - Jin Su Jeong; Florentina Cañada-Cañada; David González-Gómez (MDPI AG, 2018)
The relatively new methodology, flipped-classroom, is one of blended learning instruction methodologies in which the traditional-classroom is inverted. This methodology asserts that students can participate and engage more successfully in their class and can attain better learning when their classroom is flipped. This work presents a two-year study to measure the effects of the flipped-classroom model on the performance, perceptions, and emotions for teacher training students in science education. Particularly, this research was carried out during two courses, 2014/2015 and 2015/2016, in a general science subject. With a post-task questionnaire, we obtained the information to assess their performance, perceptions, and emotions, toward the class. The results confirmed that a statistically significant difference was found on all assessments with the flipped-classroom students, performing higher on average, showing favorable perceptions, and demonstrating positive emotions about the flipped-classroom model. Thus, the students were ready to take more courses pursuing a flipped-classroom model. The results achieved in this study show a promising inclination about the performance, perceptions, and emotions of students toward the flipped-classroom methodology, and will provide an entirely a new impetus for this relatively new instruction methodology.